MARTIN HEIDEGGER ON INAUTHENTIC EXISTENCE: THE NIGERIAN PERSPECTIVE - ThankGod Bekweri Amadi; Sotonye Big- Alabo (Journal of Social Science, 2026)
Objective: Nigeria currently faces a profound crisis of identity and sustainable development, characterized by widespread inauthenticity across its societal and individual spheres. This is more glaring in the political economy of the nation in terms of her adaptation of foreign-related, non-viable development pathways and the increasing fleeing of her citizens, especially the youths, which is popularly referred to as the Japa syndrome. The deep philosophy of Martin Heidegger supplies a moving context for understanding this complex dilemma — particularly the notion of inauthentic existence (Das Man), in which individuals immerse themselves in the indistinct crowd, giving up their unique identity and their ability to act authentically and autonomously. To achieve this, our objectives are twofold: first, to thoroughly delineate Heidegger’s understanding of inauthenticity; and second, to critically analyze how Nigeria's unsustainable development patterns and the urgent "Japa syndrome" embody this Heideggerian mode of being. Method: This study adopts the textual-analytic approach blended with hermeneutic approach, philosophically and materially locating Martin Heidegger's idea of the inauthentic and examining where it may play itself out in our contemporary Nigerian scene. Results: The study unpacks the philosophical principles behind inauthenticity as it impacts the everyday life and experiences of Nigerians, revealing a cultural propensity to live by others' “shoulds” rather than a clear essence of what gives joy and peace. Nigeria’s unsustainable development pathways and the Japa syndrome emerge as manifestations of the Heideggerian concept of “Das Man.” Novelty: The originality of this study lies in applying Heidegger’s concept of inauthentic existence (Das Man) as a philosophical framework for interpreting Nigeria’s development crisis and the Japa phenomenon, offering a deeper existential reading of contemporary socio-political realities.